Sintering behavior and microstructural characterization of aluminium copper powder compact (al-4.4cu-0.8si-0.5mgwt%) alloy prepared by powder metallurgy - Looi, Mei Yen
In this final year project, the sintering behavior and microstructural characterization of aluminium powder compaction is studied.